Drivers of phytoplankton responses to summer wind events in a stratified lake: A modeling study. Issue 4 (12th February 2022) - Mesman, Jorrit P.; Ayala, Ana I.; Goyette, Stéphane; Kasparian, Jérôme; Marcé, Rafael; Markensten, Hampus; Stelzer, Julio A.A.; Thayne, Michael W.; Thomas, Mridul K.; Pierson, Don C.; Ibelings, Bas W.
Abstract: Extreme wind events affect lake phytoplankton by deepening the mixed layer and increasing internal nutrient loading. Both increases and decreases in phytoplankton concentration after strong wind events have been observed, but the precise mechanisms driving these responses remain poorly understood or quantified. We coupled a one‐dimensional physical model to a biogeochemical model to investigate the factors regulating short‐term phytoplankton responses to summer wind events, now and under expected warmer future conditions. We simulated physical, chemical, and biological dynamics in Lake Erken, Sweden, and found that strong wind could increase or decrease the phytoplankton concentration in the euphotic zone 1 week after the event, depending on antecedent lake physical and chemical conditions. Wind had little effect on phytoplankton concentration if the mixed layer was deep prior to wind exposure. Higher incoming shortwave radiation and hypolimnetic nutrient concentration boosted phytoplankton concentration, whereas higher surface water temperatures decreased concentrations after wind events. Medium‐intensity wind events resulted in more phytoplankton than high‐intensity wind. Simulations under a future climate scenario did not show marked differences in the way wind events affect phytoplankton concentration. These findings help to better understand how wind impacts vary as a function of local environmental conditions and how climate warming and changing extreme weather dynamics will affect lake ecosystems.